PERCEPTION OF THE MIDLINE DEVIATIONS IN SMILE ESTHETICS BY LAYPERSON - Imtisal Asim; Shahab Adil; Zafar Ul Islam; Hasan Ali Raza; Ghazala; Sana Naz (Pakistan Oral & Dental Journal, 2025)
Objective: This study aimed to assess laypersons’ perception of upper dental midline deviations and explore how viewing adjacent facial structures, including lips, chin, and nose, influences the diagnosis of such deviations. Materials and Methods: A comparative cross-sectional study involving 100 patients was conducted using a non-probability consecutive sampling technique. Participants meeting inclusion criteria (age 18 years or older, no prior orthodontic treatment, normal or corrected-to-normal vision) provided written informed consent. Patients with craniofacial anomalies, severe dental malocclusions, ongoing orthodontic treatment, psychological disorders affecting self-perception, and personals having professional training in dentistry were excluded from the study. Photographs of a female subject with digitally manipulated upper dental midline deviations (0mm to 5mm) were categorized into two groups. one with adjacent facial structures (LCN) and one with lips only (L). Layperson evaluators assessed aesthetic appeal using a Visual Analog Scale (VAS). Results: Among 100 participants (mean age 31.41 Â± 8.01 years; 40% female), perception scores decreased significantly with increasing midline deviation (p < 0.001). One-way ANOVA revealed a significant association between midline deviation and perception scores (p < 0.001). Perception scores were lower in the LCN group compared to the L group. Conclusion: Laypersons were able to detect upper dental midline deviations of 1mm or more when viewing adjacent facial structures. However, they required deviations of 2mm or more when focusing solely on lips. Viewing adjacent structures influences laypersons’ perception of midline deviations.